2014
DOI: 10.11646/phytotaxa.10.1.1
|View full text |Cite
|
Sign up to set email alerts
|

An illustrated checklist of Bromeliaceae from Parque Estadual do Rio Preto, Minas Gerais, Brazil, with notes on phytogeography and one new species of Cryptanthus

Abstract: A checklist of the 14 genera and 34 species of Bromeliaceae from the Parque Estadual do Rio Preto in São Gonçalo do Rio Preto municipality, Minas Gerais state, southeastern Brazil, is presented. The Tillandsioideae was the most diverse subfamily and was found to be concentrated in rocky field areas. Bromelioideae is also a species rich subfamily, but its taxa have shown a preference to forested areas and savannas at lower altitudes. Pitcairnioideae is highlighted by its level of endemism, but has only four spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 578 publications
(17 citation statements)
references
References 13 publications
2
12
0
3
Order By: Relevance
“…The EMR has a large environmental heterogeneity, presenting a mosaic of habitats from open areas to forests, providing a high resources variety, which has also been shown in other studies (Pedralli et al 2001, Canelas and Bertoluci 2007, São Pedro and Feio 2010, São Pedro and Feio 2011. According to Rapini et al (2008) and Versieux et al (2008), the same pattern of great richness is observed for the flora of the rocky meadows of the EMR which also presents a high endemism rate.…”
Section: Discussionsupporting
confidence: 69%
“…The EMR has a large environmental heterogeneity, presenting a mosaic of habitats from open areas to forests, providing a high resources variety, which has also been shown in other studies (Pedralli et al 2001, Canelas and Bertoluci 2007, São Pedro and Feio 2010, São Pedro and Feio 2011. According to Rapini et al (2008) and Versieux et al (2008), the same pattern of great richness is observed for the flora of the rocky meadows of the EMR which also presents a high endemism rate.…”
Section: Discussionsupporting
confidence: 69%
“…Costa et al 2009 Most of the published local floras are from areas in southeastern and southern Brazil, mainly from Campos Rupestres and the Atlantic Forest region (e.g. Barros & Costa 2008;Coffani-Nunes et al 2010;Coser et al 2010;Costa & Wendt 2007;Forzza & Wanderely 1998;Guarçoni et al 2010;Luiz-Santos & Wanderley 2012;Machado 2012;Monteiro & Forzza 2008;Moura et al 2007;Siqueira Filho & Leme 2006;Versieux et al 2008Versieux et al , 2010Versieux & Wendt 2007;Wanderley & Forzza 2003;Wanderely & Martins 2007). There is a clear lack of this kind of information from the central and northern parts of the country.…”
Section: Bromeliaceaementioning
confidence: 99%
“…Notes on substrate preference (habit epiphytic, rupicolous or terrestrial), type of vegetation, as well as the geographic coordinates and altitudinal reference using GPS were taken in the field. The apparent local abundance was categorized in four classes, based on simple visual estimation (according to Versieux et al (2010), with modifications): 1) common: large populations widespread in the two types of vegetation studied; 2) occasional: small populations occurring in the two types of vegetation studied; 3) restrict: large population, limited to a particular type of vegetation. 4) rare: small population observed in a particular type of habitat.…”
Section: Data Collectionmentioning
confidence: 99%